Analysis of insulin use profile in diabetic patients in a municipal pharmacy in the interior of Bahia (Research, Society and Development, 2022)
Diabetes Mellitus (DM) corresponds to a metabolic alteration that causes permanent hyperglycemia, having as an aspect its inability to produce little or no insulin or to be resistant to it. Being classified according to its etiology in type 1 (DM1), type 2 (DM2) and gestational. This study aims to analyze the profile of insulin use in diabetic patients in a municipal pharmacy in the interior of Bahia, identifying whether its correct use occurs, the difficulties and facilities in handling the device in pen and bottle. This is a cross-sectional and descriptive study, with a quantitative approach, which analyzed the use of insulin in patients with DM treated at a Family Pharmacy unit in the Southwest of Bahia. Research participants with diabetes with insulin prescription were selected. Data were evaluated using Microsoft Excel, where descriptive analysis was performed, presented in the form of absolute and relative frequency for categorical variables. With this, it was possible to verify that most patients have a preference for insulin application using the pen method, instead of the vial with the syringe. Emphasizing the importance of monitoring these patients in order to create strategies that allow greater safety in the application of insulin, thus ensuring a better quality of life.